Analysis of Income Tax Article 21 - Alya Sadila; Galuh Tresna Murti; Nisaul Fitri; Riska Indah Viana; Syifa Syarifah Annida Chasanah (Jurnal Riset Perpajakan: Amnesty, 2023)
Income Tax Article 21 regulates withholding tax on income earned by individual taxpayers in connection with work, services, and activities. The purpose of this study is to find out the tax subject, tax object, tax withholding, and calculation of Article 21 Income Tax, and so that people who have income have a better understanding of the calculation of Article 21 Income Tax. The research method used is the qualitative research method. Based on the results of the analysis of Income Tax Article 21, it can be seen that there are different ways of calculating.